Extreme ultraviolet (EUV) source and ultra-high vacuum chamber for studying EUV-induced processes. (29th April 2015) - Dolgov, A; Yakushev, O; Abrikosov, A; Snegirev, E; Krivtsun, V M; Lee, C J; Bijkerk, F
Abstract: An experimental setup that directly reproduces extreme ultraviolet (EUV) lithography relevant conditions for detailed component exposure tests is described. The EUV setup includes a pulsed plasma radiation source, operating at 13.5 nm; a debris mitigation system; collection and filtering optics; and an ultra-high vacuum experimental chamber, equipped with optical and plasma diagnostics. The first results, identifying the physical parameters and evolution of EUV-induced plasmas, are presented. Finally, the applicability and accuracy of the in situ diagnostics is briefly discussed.